Isolation and characterization of microsatellite loci from the forage species Arachis pintoi (Genus Arachis) - Palmieri, Darío Abel [UNESP]; Hoshino, A. A. [UNESP]; Bravo, J. P. [UNESP]; Lopes, C. R. [UNESP]; Gimenes, M. A. [UNESP] (Wiley, 2002)
Arachis pintoi is an alternative to forage production in the tropics. Its germplasm comprises more than 150 accessions, that could be used to improve it. Our objective was the isolation and characterization of microsatellite loci in A. pintoi to be used to molecular evaluation of this germplasm and of A. repens (section Caulorrhizae). Seven loci were analyzed using five accessions of A. repens and 20 accessions of A. pintoi. The high variation found makes clear the high potential of this marker in genetic studies in these species. The developed markers showed total transferability to A. repens.
Keywords: Arachis pintoi; Genetic variation; Microsatellite markers; Arachis; Embryophyta; transposons